Occupational exposure of aldehydes resulting from the storage of wood pellets. Issue 6 (3rd June 2017) - Rahman, Mohammad Arifur; Rossner, Alan; Hopke, Philip K.
ABSTRACT: An exposure assessment was conducted to investigate the potential for harmful concentrations of airborne short chain aldehydes emitted from recently stored wood pellets. Wood pellets can emit a number of airborne aldehydes include acetaldehyde, formaldehyde, propionaldehyde, butyraldehyde, valeraldehyde, and hexanal. Exposure limits have been set for these compounds since they can result in significant irritation of the upper respiratory system at elevated concentrations. Formaldehyde is a recognized human carcinogen and acetaldehyde is an animal carcinogen. Thus, air sampling was performed in a wood pellet warehouse at a pellet mill, two residential homes with bulk wood pellet storage bins, and in controlled laboratory experiments to evaluate the risk to occupants. Using NIOSH method 2539, sampling was conducted in five locations in the warehouse from April–June 2016 when it contained varying quantities of bagged pellets as well as two homes with ten ton bulk storage bins. The aldehyde concentrations were found to increase with the amount of stored pellets. Airborne concentrations of formaldehyde were as high as 0.45 ppm in the warehouse exceeding the NIOSH REL-C, and ACGIH TLV-C occupational exposure limits (OELs). The concentrations of aldehydes measured in the residential bins were also elevated indicating emissions may raise indoor air quality concerns for occupants. While individual exposures are of concern the combined irritant effect of all the aldehydes is a further raise the concerns for building occupants. To minimize exposure and the risk of adverse health effects to a building's occupants in storage areas with large quantities of pellets, adequate ventilation must be designed into storage areas.